Peningkatan Pengetahuan Pasien Post Sectio Caesarea melalui Edukasi Manajemen Kesehatan Pasca Operasi - Saputri, Priska Delima; Ambarika, Rahmania (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Sectio caesarea (SC) merupakan tindakan pembedahan mayor yang memiliki risiko komplikasi fisik dan psikologis sehingga dibutuhkan manajemen kesehatan yang optimal pada fase pemulihan pasca operasi. Edukasi kesehatan menjadi bagian penting dalam pemberdayaan ibu post SC agar mampu melakukan perawatan diri secara mandiri serta mencegah komplikasi yang dapat terjadi. Objective: The purpose of this service was to increase the knowledge and independence of post sectio caesarea mothers in implementing postoperative health management through structured educational interventions in the PONEK Room of Siwa Regional Hospital. Method: This public service was conducted by health education and empowerment activities involving 20 participants (post SC mothers and families) in the PONEK Room, using interactive lectures, discussions, demonstrations, and leaflet/poster media. Analysis of priority problems used Fishbone to determine the root causes of low patient knowledge, USG to establish priority ranking (where acute pain, infection risk, and mobilization barriers were the highest), and SWOT to design strategy improvements based on strengths, weaknesses, opportunities, and threats in service implementation. Result: The results showed an increase in patient knowledge, with pre-test values averaging 60% increasing to 90% in the post-test. Participants demonstrated improved ability in wound care, early mobilization, pain control, nutrition management, and recognition of danger signs. Family involvement and support for patient recovery also increased. Conclusion: Structured health education effectively improves knowledge, attitudes, and independence of post SC mothers in postoperative health management. Optimization of continuous education and stakeholder collaboration is recommended to sustain improved recovery outcomes and patient safety in the surgical ward.